Can measures of broadband infrastructure improve predictions of economic growth? - Walter J. Mayer; Gary Madden; Xin Dang (International Telecommunications Society (ITS), 2014)
This paper investigates whether predictions of future economic growth can be improved by using standard measures of broadband infrastructure. The investigation is carried out by comparing the predictive accuracy of dynamic panel models of economic growth estimated with and without measures of broadband infrastructure. Tests of predictive accuracy are employed to test the hypothesis that measures of broadband infrastructure can improve predictions of GDP growth after controlling for standard growth determinants.
Keywords: 330; Broadband speed; economic growth; hypothesis tests; prediction